Necessity Analysis of Majalengka Picture-Based Teaching Materials Toward Historical Literacy of Elementary School - Yeni Rostini; Yuyun Dwi Haryanti; Devi Afriyuni Yonanda (MASI Mandiri Edukasi, 2026)
This research examined the need to develop illustrated instructional materials based on Majalengka’s local wisdom for school history instruction. The background of this research was the scarcity of Majalengka-based local history as a teaching resource and the limited and engaging availability of history learning for students. This descriptive qualitative research involved five teachers and ten fifth-grade students from SDN Malongpong 1, Majalengka. The researchers collected the data through interviews and classroom observation. The researchers also ensured the data's credibility through methodological triangulation. Then, the researchers analyzed the data with some steps: data reduction, data display, and data conclusion. The results found that the urgency for illustrated teaching materials based on local wisdom is meaningful and attractive as historical learning resources. This learning resource also demonstrated considerable potential to improve students’ historical literacy.